An Unusual Case of Organizing Pneumonia Associated with Influenza A and Haemoptysis - Rathnamali, B.G.A.; Liyanapathirana, C.; Undugodage, U.C.M.; Wijekoon, P.W.M.C.S.B. (Sri Lanka College of Pulmonologists, Colombo 07, 2015)
Introduction Organizing pneumonia is an inflammatory lung disease which presents sub-acutely with fever, malaise, dyspnoea and non-productive cough. Presenting with haemoptysis is rare. Here we report a patient with organizing pneumonia that presented with productive cough and haemoptysis with positive Influenza-A who responded dramatically to steroids. Case report A 58year-old woman with hypertension and type-2 diabetes presented with productive cough, heamoptysis, low-grade fever and worsening shortness of breath for one month. She was tachypnoeic and cyanosed. Oxygen saturation was 60%. There were diffuse bilateral crackles and wheezes. Initial investigations showed white-cell-count of 6x 109/L and haemoglobin of 11mg/dl. Erythrocyte-sedimentation-rate and C-reactive protein were elevated at 110mm in 1st hour and 150mg/dl respectively. Arterial-blood-gas analysis showed type-1 respiratory failure with marked hypoxaemia. Chest radiograph showed diffuse bilateral consolidations. She was given broad-spectrum antibiotics, oseltamivir and non-invasive respiratory support with no improvement. Further investigations showed no evidence of tuberculosis (negative sputum for acid-fast-bacilli, negative sputum culture for mycobacterium tuberculosis.) ANCA and ANA were negative. HIV screening was negative. Nasopharyngeal aspirate for influenza-A Polymerase-chain-reaction was positive. High resolution CT scan of chest showed extensive bilateral consolidations involving both lung fields, predominantly the periphery with intervening ground glass opacities and areas of reverse-halo-sign. A diagnosis of organizing pneumonia was made and she was started on methyl-prednisolone pulse therapy for which there was a rapid and marked improvement of hypoxaemia. She further improved oral prednisolone and currently she is followed up in outpatient clinic with no evidence of a recurrence. Discussion This patient did not improve with oseltamivir although there was evidence of Influenza-A suggesting that the virus may have triggered the process of organizing pneumonia. Furthermore hemoptysis and severe hypoxeamia are uncommon presentations of organizing pneumonia. This case illustrate that a high degree of suspicion is needed to diagnose this condition which responds very well to steroids.
Keywords: pneumonia; haemoptysis; influenza-A; steroids